Defaunation in the Anthropocene - Dirzo, Rodolfo; Young, Hillary S.; Galetti, Mauro [UNESP]; Ceballos, Gerardo; Isaac, Nick J. B.; Collen, Ben (Amer Assoc Advancement Science, 2014)
We live amid a global wave of anthropogenically driven biodiversity loss: species and population extirpations and, critically, declines in local species abundance. Particularly, human impacts on animal biodiversity are an under-recognized form of global environmental change. Among terrestrial vertebrates, 322 species have become extinct since 1500, and populations of the remaining species show 25% average decline in abundance. Invertebrate patterns are equally dire: 67% of monitored populations show 45% mean abundance decline. Such animal declines will cascade onto ecosystem functioning and human well-being. Much remains unknown about this “Anthropocene defaunation”; these knowledge gaps hinder our capacity to predict and limit defaunation impacts. Clearly, however, defaunation is both a pervasive component of the planet’s sixth mass extinction and also a major driver of global ecological change.
Keywords: Decomposition; Defaunation; Ecosystem; Environmental aspects and related phenomena; Environmental change; Environmental impact; Extinct species